2010
DOI: 10.4000/vertigo.10038
|View full text |Cite
|
Sign up to set email alerts
|

Urbanisation et viabilité de l'activité maraîchère : cas d'une ville à statut particulier au Bénin (Parakou)

Abstract: Les villes des pays en développement sont en pleines mutations caractérisées par une augmentation de la taille de la population et une urbanisation. Ces deux facteurs les soumettent à deux défis majeurs. Le premier concerne l’approvisionnement des populations en produits alimentaires frais et le deuxième est relatif au problème foncier auquel font face ceux qui produisent ces produits alimentaires. Ce papier se consacre à l’étude des contraintes foncières auxquelles sont confrontés les maraichers urbains. La v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
2
0
3
Order By: Relevance
“…Market gardening is of greater interest to a certain category of people seeking for employment, food and financial sovereignty. In Benin for example, Nouatin et al (2010) showed that market gardening production was the main activity and sole source of income for market gardeners. Given the profitability of the activity, young school dropouts are increasingly interested in market gardening and this is in line with the results of Ahouangninou (2013).…”
Section: Discussionmentioning
confidence: 99%
“…Market gardening is of greater interest to a certain category of people seeking for employment, food and financial sovereignty. In Benin for example, Nouatin et al (2010) showed that market gardening production was the main activity and sole source of income for market gardeners. Given the profitability of the activity, young school dropouts are increasingly interested in market gardening and this is in line with the results of Ahouangninou (2013).…”
Section: Discussionmentioning
confidence: 99%
“…The overall growth of the population of the city can be adjusted to an exponential function " Figure 3" with respect to its variation since it was at 14,000 and 60,000 inhabitants between 1961 and 1979 [25]. At the level of administrative division, the disparity of the spatial variation of average growth (Figure 2) is a component of the growth ratio [21].…”
Section: Evaluation Of Cast Zipf's Law In Parakou Between 1979 and 2013mentioning
confidence: 99%
“…En Afrique subsaharienne, le maraîchage urbain est une activité qui joue un rôle important face aux problèmes liés à la croissance démographique galopante en milieu urbain (Nouatin et Bachabi, 2010 ;Kouakou et al, 2019). En effet, de la production à la vente, les activités maraîchères en milieu urbain permettent non seulement de résorber les problèmes de la sécurité alimentaire, mais aussi de réduire le taux de chômage et de contribuer au recyclage des déchets organiques utilisés pour la fertilisation des sols (Tella et al, 2013 ;Bouda et al, 2018).…”
Section: Introductionunclassified
“…Au Congo, le maraîchage urbain constitue la principale source d'approvisionnement des marchés des villes en légumes frais (Nzoussi et Li, 2015 ;Mizhaire et Ofouémé, 2019). Le maraîchage à Brazzaville est essentiellement pratiqué sur des sols ferrallitiques et hydromorphes (Gakosso, 2015).…”
Section: Introductionunclassified